Rural land dispossession in China and India - ANDREAS, Joel (Institutional Knowledge at Singapore Management University, 2020)
The twelve articles in this special issue feature the work of scholars studying the dispossession of rural land in China and India. Each offers new insights about the extent and patterns of dispossession, the complex dynamics driving it, the consequences for farmers, as well as the factors shaping resistance or compliance. Although each article treats developments within one country, the collection helps uncover features common to rural land dispossession in China and India, and illuminates differences that shape the processes of dispossession in each country. Comparison of the two countries helps us to not only understand the future implications of this enormously important issue for economic growth, social inequality and politics in both countries, but also contributes insights useful for understanding this issue elsewhere in the world.